Morphological characterization of aqueous tin oxyhydroxide gel - Helena Pulcinelli, Sandra [UNESP]; Valentim Santilli, Celso [UNESP]; Pierre Jolivet, Jean; Tronc, Elisabeth (Elsevier, 1994)
Light scattering, electron microscopy and X-ray diffraction are used to determine the morphology and size of particles in diluted aqueous gel of tin (IV) oxyhydroxide. Data show that the gel is composed of spherical 2-3 nm sized crystalline particles aggregated as rigid branched chains. It is suggested that stiffness of chains results from dissolution-precipitation equilibria and chemical bonding between particles within the chains. © 1994.
Keywords: Agglomeration; Dissolution; Gels; Light scattering; Microscopic examination; Microstructure; Morphology; Oxides; Particle size analysis; Phase equilibria; Precipitation (chemical); X ray analysis; Aqueous gels; Chain stiffness; Chemical bonding; Tin oxyhydroxide; X ray diffraction; Tin compounds